Faktor-faktor yang Mempengaruhi Kinerja Usaha Sapi Perah Rakyat di Kecamatan Grati Kabupaten Pasuruan - Dimas Pratidina Puri Hadiani; Enike Dwi Kusumawati; Rama Sukma Nurhadi (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2020)
This research was conducted at the Livestock Farming Cooperative (KUTT) of Suka Makmur on Jl. Raya Semambung Grati Desa Grati Pasuruan Regency on September 1, 2018 - September 25 2018. The purpose of this study was to determine the factors that influence the business performance of people's dairy cows in Grati District, Pasuruan Regency. The population used is dairy farmers who are members of KUTT in Grati Village, Pasuruan Regency with questionnaires as many as 100 people who take ownership of livestock under 5 heads and more than 2 dairy cows. The research method was carried out by the surve method, which is taking samples from the population of dairy farmers with a questionnaire as a data collector. The results of this study are Y = -31,729 + 0,561 X1 + 5,454 X2 + 2,087 X3 + 1,628 X4 + 8,215 X5 + (-0,117 X6) + 0,406 X7 + (-0,922 X8) +0,160 X9 and the R squared value is 0,451 this means that the business performance of dairy cows can be explained by variable X of 45.1% and the remaining 54.9% is caused by sapilactation and extensive cage factors. The factors that influence the performance of dairy cows in the Grati farm in Pasuruan Regency, from this result the most influential variable is the number of lactation cows and cage area.